Dynamics of the Nadran Tradition in Gunung Jati District Cirebon Regency 1999-2019 - Siti Aminatul Maryam Isnaeni; Muzakki Bashori (Historia, 2026)
During the period of 1999-2019, the Nadran tradition in the Gunung Jati sub-district, Cirebon Regency, underwent various changes. This tradition, which comprises three processions Sedekah Laut, Sedekah Bumi, and Arak-arakan was the focus of a historical study aimed at understanding its meaning for the local community and its development over time. The research, which utilized primary and secondary sources along with historical methodology (heuristics, criticism, interpretation, and historiography), found that the tradition faced several challenges, including disputes among participants, a lack of security, and limited funding. Despite these difficulties, the community continued to hold the Nadran tradition as a means of cultural preservation and an expression of gratitude.Â